Steps to Make Miracles Possible - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2023)
When it comes to living promising and at the same time ethically positive behaviors, one cannot avoid the great teachers of mankind in history. This article introduces the "Old One" from China, LaoTse/Laozi, and the Jewish Rabbi Hillel. Laozi described the basic principle of Dao, doing through non-doing. In his teachings there are many hints on how to live stress-free and successfully. 12 mnemonics are presented. Hillel, even before Jesus the Christ, described the Golden Rule: "Love your neighbor as yourself". It is a contrast to the Old Testament "eye for an eye, tooth for a tooth." Put the two teachings together and the result is an ethic that could solve many of the problems of our time, in the individual as well as on the world stage.